Flower and fruit development of Syzygium pycnanthum Merr. & L.M. Perry - DEDEN MUDIANA; ESTI ENDAH ARIYANTI (Biodiversitas Journal of Biological Diversity, 2010)
Mudiana D, Ariyanti EE (2010) Flower and fruit development of Syzygium pycnanthum Merr. & L.M. Perry. Biodiversitas 12: 124-128. Flower formation is a process of flowering plant in order to produce the next generation. Flower plays a major role in pollination and fertilization as early stage of fruit and seed formation. Syzygium pycnanthum is a member of family Myrtaceae or known as ‘Jambujambuan’ family. The research aim was to observe the development process of flowering and fruiting phase of S. pycnanthum at Purwodadi Botanical Garden. It has been noted that this species has ten (10) stages of flowering and fruit development, namely flower bud initiation, flower bud fully emerge, unfolding calyx, visible corolla, bud starts blooming, early blooming, perfectly blooming, perianths and anthers fall, early fruit structure and ripe fruit. All these stages require 80-89 days.Key words: Syzygium pycnanthum, flower and fruit development.